Improving Financial Performance through the Implementation of Simple Accounting Systems in MSMEs in Ciruas, Serang Regency - Putri Wulandari; Ingga Maulana; Rismawati Rismawati (Abdimas Paspama, 2025)
This community service program aims to improve the financial performance of micro, small, and medium enterprises (MSMEs) in Ciruas, Serang Regency, through the application of simple accounting systems. Many MSMEs still rely on manual financial records, lack basic accounting knowledge, and do not utilize available technology. These challenges hinder their ability to monitor cash flow, calculate profits, and make strategic business decisions. The program involves direct interviews, field observations, and hands-on training sessions. Participants were introduced to a simple accounting template using spreadsheet applications that can be operated via mobile devices. The results show an increased awareness and understanding of financial management among the MSME participants. Several businesses have begun to adopt digital bookkeeping methods and now recognize the importance of transparent and accurate financial reports. This initiative demonstrates that with proper guidance and practical tools, MSMEs can enhance their financial efficiency and achieve better business sustainability.